Type III hypersensitivity reactions to a B cell epitope antigen are abrogated using a depot forming vaccine platform. Issue 1 (2nd January 2018) - MacDonald, Lisa D.; MacKay, Alecia; Kaliaperumal, Valarmathy; Weir, Genevieve; Penwell, Andrea; Rajagopalan, Rajkannan; Langley, Joanne M.; Halperin, Scott; Mansour, Marc; Stanford, Marianne M.
ABSTRACT: Peptide antigens are combined with an adjuvant in order to increase immunogenicity in vivo . The immunogenicity and safety of a RSV vaccine formulated in a novel oil-based platform, DepoVax™ (DPX), was compared to an alum formulation. A peptide B cell epitope derived from RSV small hydrophobic ectodomain (SHe) served as the antigen. Both vaccines induced SHe-specific antibodies after immunization of mice. A single dose of the DPX-based formulation resulted in anti-SHe titres for up to 20 weeks. Boosting with Alum-SHe, but not with DPX-SHe, led to unexpected clinical signs such as decreased activity, cyanosis and drop in body temperature in mice but not in rabbits. The severity of adverse reactions correlated with magnitude of SHe-specific IgG immune responses and decreased complement component 3 plasma levels, indicating a type III hypersensitivity reaction. By RP-HPLC analysis, we found that only 8–20% of the antigen was found to be adsorbed to alum in vitro, indicating that this antigen is likely released systemically upon injection in vivo . Clinical signs were not observed in rabbits, indicating the response correlates with peptide dose relative to size of animal. These results suggest that peptide antigens targeted to produce B cell mediated response may result in increased incidence of type III hypersensitivity reactions when delivered in non-depot forming vaccines. The DPX formulation induced strong antibody titres to the antigen without causing adverse events, likely due to the strength of the depot in vivo, and demonstrates the potential safety and immunogenicity of this platform for B cell peptide antigens.